Takotsubo cardiomyopathy caused by acute respiratory stress from extubation: A case report. Issue 48 (December 2017) - Taniguchi, Kohei; Takashima, Syogo; Iida, Ryo; Ota, Koshi; Nitta, Masahiko; Sakane, Kazushi; Fujisaka, Tomohiro; Ishizaka, Nobukazu; Umegaki, Osamu; Uchiyama, Kazuhisa; Takasu, Akira
Abstract: Rational: Takotsubo cardiomyopathy (TCM) is a transient systolic dysfunction of the left ventricular apex without stenosis of coronary arteries and is induced by various psychological and physical factors. TCM sometimes causes lethal complications such as arrhythmia, thrombogenesis, and even cardiac rupture, and thus it should be diagnosed appropriately and managed carefully. Intensive care unit (ICU) patients are exposed to overstress during the treatment process and therefore can are at potential risk for TCM. Patient concerns: The patient was diagnosed as having pneumonia because of influenza A virus mixed with bacteria and underwent intensive care with intubation and mechanical ventilation in the ICU. His respiratory condition soon improved, and so extubation was carried out; however, redeterioration with pulmonary edema occurred at half of a day following extubation. Diagnosis: The chest x-ray revealed pulmonary edema. The electrocardiogram pattern significantly changed with time, and the echocardiogram showed weakness of wall motion around the left ventricular apex. Hence, to confirm the diagnosis, we performed cardiac catheterization immediately, with the results showing a Takotsubo-like form at the systolic phase without significant stenosis of the coronary arteries. Intervention: The patient was reintubated with administration of catecholamine for decreasing blood pressure caused by left ventricular dysfunction. Also, diuretics for pulmonary edema and anticoagulants for prevention of thrombogenesis were administered. Outcomes: As the respiratory condition improved with stabilization of cardiovascular hemodynamics, reextubation was done at ICU day 11 and was discharged from the ICU at ICU day 15. The patient was subsequently treated for pneumonia after leaving the ICU but suffered from repetitive aspiration pneumonia and was finally transferred to another hospital at hospital day 111. Lessons: TCM should be considered especially under the situation of intensive care, and prompt diagnosis should be followed by appropriate management. Abstract : Supplemental Digital Content is available in the text